2017
DOI: 10.3171/2016.12.peds1668
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance survey of family history in children with neural tube defects

Abstract: OBJECTIVE Although there are known risk factors for the development of neural tube defects (NTDs), little is known regarding the role of family history. The authors' goal in this study is to describe the family history in their population of patients with NTDs. METHODS Surveys were completed for 254 patients who were accompanied by their biological mother during their annual visit to the multidisciplina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…We found that positive history of another relative with NTDs confers up to 68‐and 22‐times greater risk of having anencephaly or OSB, respectively, and together with consanguinity, that confers a 14‐fold increased risk of having OSB (Table 3), constitute a robust indicator of genetic susceptibility for ONTDs, despite the fact that they have infrequently been included in other epidemiological studies 34 . Patterns of transmission in most families with NTDs fit with a multifactorial model, although with a low degree of familial aggregation 1 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We found that positive history of another relative with NTDs confers up to 68‐and 22‐times greater risk of having anencephaly or OSB, respectively, and together with consanguinity, that confers a 14‐fold increased risk of having OSB (Table 3), constitute a robust indicator of genetic susceptibility for ONTDs, despite the fact that they have infrequently been included in other epidemiological studies 34 . Patterns of transmission in most families with NTDs fit with a multifactorial model, although with a low degree of familial aggregation 1 .…”
Section: Discussionmentioning
confidence: 82%
“…Consanguinity raises the risks because increases the number of genes in common related to NTDs, such as those implicated in metabolic pathways of folate or glucose, among others 18 . Thus, members of these families are recognized as less responsive to prevention with FA supplements, highlighting the role of genetics in the pathogenesis of ONTDs, 34 although it should not be forgotten that they also share the same adverse environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The association of cyst with the family history was statistically significant but due to limited number of samples can't be conclusive. Dupepe 29 et al in2017 found that among patients of NTDs the general prevalence of family history was 16.9% of which 3.1% were seen in first degree relatives. The prevalence of MMC among all NTDs in terms of family history was 17.7% with 3.8% in first degree relatives.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we found that among the fifty cases, only one patient showed the positive family history. Dupépé etal stated that there is relatively strong association of family history in neural tube defects 23 . It is quite possible that due to small sample size our results differ from them.…”
Section: Discussionmentioning
confidence: 99%